2017
DOI: 10.3390/en10111919
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Coal Grain Size on Sorption Capacity with Respect to Propylene and Acetylene

Abstract: Propylene and acetylene are released to mine air with the increase in the temperature of self-heating coal. Concentrations of these gases in mine air are applied as indicators of the progress of the self-heating process. Hydrocarbons emitted from the self-ignition center are sorbed on coal, while migrating through the mine workings. Coal crushed during the mining process is characterized by a high sorption capacity, which facilitates the sorption phenomena. This results in the decrease in hydrocarbons content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
(23 reference statements)
1
11
0
Order By: Relevance
“…Coal is an extremely heterogeneous porous material containing both organic macerals and inorganic mineral matter [1]. The macromolecule structure of coal macerals offers plenty of adsorption sites for gaseous and liquid adsorbates [2][3][4]. In addition, the amorphous surface of coal enriches functional groups, possessing strong adsorption capacity for polar molecule adsorbates [5][6][7], such as water vapor.…”
Section: Introductionmentioning
confidence: 99%
“…Coal is an extremely heterogeneous porous material containing both organic macerals and inorganic mineral matter [1]. The macromolecule structure of coal macerals offers plenty of adsorption sites for gaseous and liquid adsorbates [2][3][4]. In addition, the amorphous surface of coal enriches functional groups, possessing strong adsorption capacity for polar molecule adsorbates [5][6][7], such as water vapor.…”
Section: Introductionmentioning
confidence: 99%
“…Moisture content was determined in accordance with the PN-80/G-04511 standard and ash content in accordance with the PN-80/G-04512 standard. Hard coal can be very heterogenous with respect to chemical and petrographic composition, even over short distances (<1 km) [23,24]. The use of a relatively large, solid sample, with a mass of approximately 20 g, allows for better representation of the coal bed being studied, compared to literature data, where, very often, small samples, often not exceeding 1 g, are used.…”
Section: Research Materialsmentioning
confidence: 99%
“…The influence of coal particle size on the sorption capacity as regards mine gases has been previously studied. Yet most of these measurements were performed with the use of carbon dioxide and methane in respect to enhanced coalbed methane recovery or with the use of single gases, eg, propylene and acetylene as an adsorbate . In turn, studies on the sorption of the mixture of ethylene, propylene, propane, and ethane have been previously performed but only on coals with the grain size of 0.5 to 0.7 mm.…”
Section: Introductionmentioning
confidence: 99%
“…Yet most of these measurements were performed with the use of carbon dioxide and methane in respect to enhanced coalbed methane recovery 21,22 or with the use of single gases, eg, propylene and acetylene as an adsorbate. 23 In turn, studies on the sorption of the mixture of ethylene, propylene, propane, and ethane have been previously performed but only on coals with the grain size 8,13,24 of 0.5 to 0.7 mm. In the course of the experimental works, it was observed that propylene was the gas that sorbed in the larger amount and gained the sorption equilibrium in the longest time in comparison with ethane, ethylene, and propane.…”
Section: Introductionmentioning
confidence: 99%